Pasárgada reconquistada?: estudo sobre o processo de implementação das Unidades de Polícia Pacificadora - Fichino, Daniela Alessandra Soares (2012)
This thesis offers the reader some narratives about the Pacifying Police Units, collected amongst the actors that experience the process of its implementation. In the first chapter, I explore how diferent speeches organize different policing practices observed in the city of Rio de Janeiro, symbolically structured in a counterpoint between "war" and "peace." In the second chapter, I describe different uses of the term "UPP", and what each can reveal about this project of public safety. In the third chapter, I present an account on the perceptions of the residents of a "pacified" favela. I do not intend to fix a meaning to the experience of the Pacifying Police Units, but to describe conflicting senses, opening the range of interpretive possibilities.